Vibrating moistening of wheat grain - Chornyi, Valentyn; Kharchenko, Yevgen (My University, 2023)
The article experimentally established the influence of amplitude, frequency and duration of processing on the efficiency of vibratory wetting of wheat. With increasing amplitude and frequency of oscillations, as well as the duration of processing, the increase in moisture in the grain increases nonlinearly. With oscillation amplitudes of 10 and 20 mm and constant frequency of 10 Hz and processing duration of 8 min., Wheat grain increased moisture by 2.1%. Processing time more than 8 min. does not increase the moisture content of wheat. The largest increase in moisture in wheat was observed at an oscillation frequency of 12 Hz and an amplitude of 20 mm and a treatment duration of 5 min. Increasing the oscillation frequency more than 12 Hz did not lead to an increase in wheat moisture. It was found that the load does not affect the efficiency of moistening wheat grain. В статті встановлено вплив амплітуди, частоти і тривалості обробки на ефективність вібраційного зволожування пшениці. Зі збільшенням амплітуди і частоти коливань, а також тривалості обробки, вологість пшениці нелінійно збільшується. При амплітудах коливань 10 і 20 мм і постійною частотою 10 Гц і тривалості обробки 8 хв., зерно пшениці збільшило вологість на 2,1 %. Тривалість обробки більше 8 хв. не збільшує вологість пшениці. Найбільша вологість пшениці спостерігалась при частоті коливань 12 Гц, амплітуді 20 мм і тривалості обробки 5 хв. Збільшення частоти коливань більше 12 Гц не приводило до збільшення вологості пшениці. Встановлено, що навантаження не впливає на ефективність зволоження зерна пшениці.
Keywords: вібраційне зволоження; wheat moisture; vibration humidification; вологість пшениці; кафедра технології зберігання і переробки зерна; кафедра процесів і апаратів харчових виробництв